The effects of liberalization and trade related policies on fisheries and measures required for their sustainable development in the CARIFORUM/CARICOM region - Rankine, Lloyd B. (CFRM Secretariat Belize CityBZ, 2004)
Examines global developments and their possible impact on Caribbean fishery resources.